Constant lock circuit for DC micro-grid system - Mohammed, Asaad Abduljabbar (2017)
The escalating rates of fossil fuels have enforced researchers to seek renewable energy systems. Power generation from fossil fuels may not be possible for very long as they are depleting. Recently, the researchers have been interested in the techniques of exploiting renewable energy sources such as solar, hydro, wind, etc. The energy conversion from water flow streams to electrical energy via Pico turbine generator is the only solution. The only disadvantage of hydro energy is the seasonal variations when it cannot generate enough power to meet the load demand. Also, the changing of water flow rates causes a variable output voltage. In this renewable system, continuous power flow to meet load demand is not possible. For integration of REs to optimal results, an excellent option for energy production can be obtained by using a microgrid system by combining the renewable energy source with a backup source such as a utility grid. Therefore, this thesis develops DC micro-grid control strategies based on providing continuous load power regardless of the generated power and load demand. The comparison between generated power and load consumption leads the monitoring system to determine the proper mode that the system should follow. Three modes come into view during DC micro-grid operations. These operational scenarios are the standalone scenario, grid scenario, and feedback scenario. A simulation of the DC micro-grid in order to provide a continuous load demand based on using a CLC which is keeping the DC link at a 24v constant value is designed. Due to the ongoing interaction between the fluctuating weather conditions and load demands in a DC micro-grid, each source needs to be in a highly precise control regulation to link with the DC link node. So,it requires voltage compatibility of all sources associated with the DC link bus for keeping the stability of the DC link at a constant value, Moreover, parallel sources connection for sharing power at a DC micro-grid have problems such as reverse current, and degradation of power conversion efficiency, due to a slight difference between output voltages. For all the above, there is a need for a new interface block control to deal with these problems. For this, an algorithm system strategy for utilizing a Constant Lock Circuit in the DC micro-grid aims at maintaining a constant DC link voltage at the desired constant value of 24v to ensure high stability voltage and current without any ripple. Furthermore, it is deemed relevant to give priority to the renewable energy production for supplying load extracting maximum power from the REs. Moreover, it is also necessary to provide an adequate load demand regardless the power generation amount for satisfying an easy connection between two parallel sources for sharing power. On top of that, the power that the load needs from the backup source to meet load demand should be compensated to export the surplus RE power to the backup source. The models of the DC micro-grid with CLC system are simulated in Proteus8 Professional. Results obtained from simulations have proven that the proposed algorithm system strategy have achieved its aims through keeping constant 24v with percentage error 0.059%.